Analisis Pengaruh Kualitas Material terhadap Kuat Tekan Beton pada Pembangunan Gedung Bertingkat - Andika Candra; Rezi Munizar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Concrete is the primary material used in the construction of high-rise buildings because it can withstand compressive loads and ensure long-term structural stability. This study aims to analyze the effect of constituent material quality on concrete compressive strength through a laboratory experimental approach. The research method utilized two variations of concrete mixes with a design strength of fc′=30 MPa: one using standard-grade materials and the other using substandard materials with high aggregate silt content and suboptimal coarse aggregate gradation. Tests were conducted on 150 × 300 mm cylindrical specimens at 7, 14, and 28 days using a compression testing machine. The results showed that concrete made with standard materials achieved a compressive strength of 31.2 MPa, while concrete made with substandard materials reached only 24.5 MPa—a 18.4% reduction from the design strength. These findings indicate that material quality plays a crucial role in determining concrete density, internal bond strength, and the structural reliability of multi-story buildings.